Erosi Sumpremasi Konstitusi dalam Negara Hukum Indonesia: Analisis Kritis Terhadap Parktik Politik Hukum Kontemporer - Anderias Pageru; Ghina Salsabila Aven (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The supremacy of the constitution is a fundamental principle of the rule of law, positioning the constitution as the highest legal norm within the constitutional system. However, in contemporary Indonesian constitutional practice, this principle faces significant challenges due to the dynamics of legal politics. This study aims to critically analyze the erosion of constitutional supremacy in Indonesia as a state governed by law and to examine contemporary legal-political practices that contribute to the weakening of the constitution’s authority. This research employs a normative juridical method with statutory, conceptual, and case approaches. Legal materials were collected through library research, including primary, secondary, and tertiary sources, and analyzed using qualitative descriptive analysis. The findings indicate that the erosion of constitutional supremacy results from the dominance of political interests in law-making processes, weak compliance with Constitutional Court decisions, and the instrumentalization of law within political practices. These conditions undermine the function of the constitution as a limitation on state power and as a safeguard for citizens’ constitutional rights. This study concludes that strengthening constitutional supremacy requires a legal-political orientation grounded in constitutionalism, consistent adherence to Constitutional Court decisions, and the development of a strong constitutional culture among state institutions.